Inhibiting Autophagy by Chemicals During SCAPs Osteodifferentiation Elicits Disorganized Mineralization, While the Knock-Out of Atg5/7 Genes Leads to Cell Adaptation - Damien Le Nihouannen; Claudine Boiziau; Sylvie Rey; Nicole Agadzhanian; Nathalie Dusserre; Fabrice Cordelières; Muriel Priault; Helene Boeuf (Cells)
SCAPs (Stem Cells from Apical Papilla), derived from the apex of forming wisdom teeth, extracted from teenagers for orthodontic reasons, belong to the MSCs (Mesenchymal Stromal Cells) family. They have multipotent differentiation capabilities and are a potentially powerful model for investigating strategies of clinical cell therapies. Since autophagy—a regulated self-eating process—was proposed to be essential in osteogenesis, we investigated its involvement in the SCAP model. By using a combination of chemical and genetic approaches to inhibit autophagy, we studied early and late events of osteoblastic differentiation. We showed that blocking the formation of autophagosomes with verteporfin did not induce a dramatic alteration in early osteoblastic differentiation monitored by ALP (alkaline phosphatase) activity. However, blocking the autophagy flux with bafilomycin A1 led to ALP repression. Strikingly, the mineralization process was observed with both compounds, with calcium phosphate (CaP) nodules that remained inside cells under bafilomycin A1 treatment and numerous but smaller CaP nodules after verteporfin treatment. In contrast, deletion of Atg5 or Atg7, two genes involved in the formation of autophagosomes and essential to trigger canonical autophagy, indicated that both genes could be involved differently in the mineralization process with a modification of the ALP activity while final mineralization was not altered.